Exploration of physics principles in bola rai' design based on local knowledge - Fajriyani, Fajriyani; Anugra, Novia; Fadila, Fadila; Putri, Amelia (Universitas Muhammadiyah Mataram, 2025)
Exploration of Physics Principles in Bola Rai' Design Based on Local Knowledge. This study aims to explore the application of physics principles in the design of Bola Rai’, a floating house constructed based on local knowledge of the community around Lake Tempe. The research employs a qualitative descriptive approach, utilizing interviews, observations, and documentation techniques in Dusun Salomate, Limpomajang Village, Soppeng Regency. Primary data from interviews and observations were supplemented with secondary sources from literature. The analysis reveals that the design of Bola Rai’ applies physics principles such as Archimedes' principle, hydrostatic pressure, weight, and pressure within the raft structure. Additional physics concepts are applied to the house’s pillars, including weight, Newton's laws, and pressure. The walls demonstrate principles of aerodynamics, heat transfer, thermal conductivity, and Pascal’s law, while the roof structure incorporates principles of pressure, weight, and thermal conductivity. The study concludes that physics principles have been effectively integrated into the design of Bola Rai’ through the adaptation of local knowledge, suggesting its potential as a source for contextual physics learning.